2010
DOI: 10.1093/jac/dkq369
|View full text |Cite
|
Sign up to set email alerts
|

Tribal ethnicity and CYP2B6 genetics in Ugandan and Zimbabwean populations in the UK: implications for efavirenz dosing in HIV infection

Abstract: Among Zimbabweans, LoF haplotypes constitute the majority of CYP2B6 alleles and are significantly higher in prevalence compared with Ugandans. Frequencies of LoF haplotypes and SNPs in Ugandan Nilotics appear to lie between those of Zimbabweans and Ugandan Bantus. These findings may have relevance to pharmacokinetics and dosing of efavirenz in African populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 27 publications
1
27
1
1
Order By: Relevance
“…Although cytochrome P450 enzymes play a limited role in metabolizing NRTIs, they do contribute to variability in response to NNRTIs and PIs. The best described enzyme in this context is CYP2B6, which plays a pivotal role in phase I metabolism of efavirenz and to a lesser extent nevirapine [12][13][14][15][16][17]. Decreased metabolism of these NNRTIs results in increased plasma levels and related side effects, including neurotoxicity in the case of efavirenz, and hepatotoxicity when nevirapine is used.…”
Section: Cyp2b6 Cyp2a6 and The Management Of Hiv/aidsmentioning
confidence: 99%
“…Although cytochrome P450 enzymes play a limited role in metabolizing NRTIs, they do contribute to variability in response to NNRTIs and PIs. The best described enzyme in this context is CYP2B6, which plays a pivotal role in phase I metabolism of efavirenz and to a lesser extent nevirapine [12][13][14][15][16][17]. Decreased metabolism of these NNRTIs results in increased plasma levels and related side effects, including neurotoxicity in the case of efavirenz, and hepatotoxicity when nevirapine is used.…”
Section: Cyp2b6 Cyp2a6 and The Management Of Hiv/aidsmentioning
confidence: 99%
“…The CYP2B6 516T/T genotype is especially important in metabolism of anti-cancer and anti-HIV drugs and has been associated with diminished enzyme expression levels resulting in lower efavirenz and nevirapine clearance (50-60%), increased steady-state plasma concentrations and a high frequency of central nervous system (CNS) adverse effects [46,[52][53][54][55][56][57][58]. Interethnic variability in response to the anti-TB drug rifampicin has been explained by variability in CYP2B6 and N-acetyltransferase type 2 (NAT2) expressions [19,59].…”
Section: Implications For Global Pharmacogeneticsmentioning
confidence: 99%
“…A high allele frequency of 49% for the *6 allele was seen in HIV patients in Zimbabwe (Nyakutira et al, 2008). The CYP2B6*6 allele frequency also differed significantly between a Zimbabwean and a Ugandan population, being 48 and 17% (p50.004), respectively (Jamshidi et al, 2010).…”
Section: Cyp2b6*6 (516g4t and 785a4g)mentioning
confidence: 92%
“…In a study by Radloff et al (2013), eight novel functionally uncharacterized nonsynonymous variants were found in the CYP2B6 gene in a Rwandese population, and it was demonstrated that four of these variants resulted in complete or almost complete loss of function. Three novel SNPs in the CYP2B6 gene were found in a Zimbabwean population (341T4C, 444G4T and 1158A4G), and two novel SNPs in a Ugandan population (856C4T and 1459C4A; Jamshidi et al, 2010). These findings demonstrate the potentially large number of African specific alleles that might exist.…”
Section: Pharmacogenetics In Africamentioning
confidence: 96%
See 1 more Smart Citation